Cigarette Smoking Habits among University Students: Prevalence and Associated Factors - Junaid Jamshed; Muhammad Mushtaq Khan; Zahid Latif (International Journal of Public Health Science (IJPHS), 2017)
Smoking is the main cause of morbidity and mortality in the world and is estimated to kill 5 million people each year worldwide. If current patterns of tobacco consumption continue, smoking will kill more than 8 million people each year globally by the year 2030, with 80% of these deaths in the developing countries. This study aimed to determine the prevalence and associated factors of cigarette smoking among male university students in Muzaffarabad, Pakistan. A descriptive cross-sectional study was conducted among 542 male students at University of Azad Jammu & Kashmir in Muzaffarabad from July to December 2015. The socio-demographic characteristics and cigarette smoking behavior of the students were measured by using a standardized pre-tested self-administrated validated questionnaire in English. The overall prevalence of cigarette smoking among students was found to be 49.4%. The mean age of starting cigarette smoking was 19.2 2.73 years. Age, marital status and education were found significantly associted with cigarette smoking behavior (p-value<0.05). The most common reason for cigarette smoking was stress alleviation (35.0%) followed by peer pressure (24.5%). As cigarette smoking is considerably higher among students. There is a need to develop effective tobacco control measures among university students in Muzaffarabad.